Combining Ability for Vigour Characters under Normal and Saline Environments in Ethiopian Mustard - Thakral, N K; Singh, Hari (Annals of Arid Zone, 2016)
Combining ability analysis or 6 x6 diallel or Ethiopian mustard (Brassica cannata A. Braun) ror germination per cent, speed or germination and seedling vigour under normal and two saline environments (125 and 175 meq I-1) revealed that both additive and non-additive type or gene errects were involved in the inheritance or these characters. The predictability ratio indicated greater importance or non-additive type or gene actions, whereas additive genetic errect was important of percent germination under 125 m I-1 salinity level. BC2 and HC7 were the best general combiners. The crosses BC2 x C6YS7B and HC 15 x HC Z were the best combinations ror all the three characters over theÂ· environments.